Obraz życia kobiet na podstawie "Lizystraty" oraz "Sejmu kobiet" Arystofanesa - Kowalska, Martyna (Collectanea Philologica, 2024)
It is common knowledge that in ancient times women did not have many rights that were assigned only to men, such as the right to education, owning their own property or freely choosing a partner. The aim of the article is to present the image of the life of women in ancient Greece, with particular emphasis on the citizens of Athens during the Peloponnesian War and after its end, based on two comedies by Aristophanes: Lysistrata and Assemblywomen. By highlighting some stereotypes regarding women, the comedy writer draws attention to the chaos that prevails in political matters for which men are responsible. Women make a kind of transition from the zone of oikos intended for them to the zone of polis, becoming the main characters of comedy.